Towards knowledge-driven cross-species extrapolation. (2016) - Thiel, Christoph; Hofmann, Ute; Ghallab, Ahmed; Gebhardt, Rolf; Hengstler, Jan G.; Kuepfer, Lars
Abstract : The transition from preclinical research to clinical phases is a crucial step in pharmaceutical development. In phase I, a new molecular entity is for the first administered to humans, after year-long development in in vitro and in preclinical animal models. However, a significant number of projects is closed during such first-in-man trials, mostly due to reasons of toxicity. This requires for new approaches in pharmaceutical development through computational modelling and through the selection of explanatory animal models, respectively, in order to support the transition from preclinical to clinical phases. In this review we will discuss the basic challenges in cross-species extrapolation before presenting some recent developments in this field as well as future perspectives.